Peningkatan Keterampilan Mengajar Mahasiswa Praktik Pengalaman Lapangan (PPL) Melalui Penerapan Lesson Study Secara Terpadu di SMP Negeri 9 Jember - Mochammad Iqbal (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2016)
Field Experience Practice Program or Program Praktik Pengalaman Lapangan (PPL) is a mandatory program to be followed by FKIP students of the University of Jember. As a field supervisor lecturer, in order to improve the quality and effectiveness of PPL in Junior High School 9 of Jember, I launched integrated PPL program with Lesson Study (LS). Junior High School 9 of Jember, as a partner in the development of the LS school in Jember by FKIP UNEJ, providing full support to the implementation of LS-based PPL. The support not only the license to undergo LS based PPL, but also school provide policies that encourage teachers to officials actively involved in the implementation of integrated LS-based PPL. This implementation is expected to enhance the effectiveness of the implementation of the PPL so as to improve the teaching skills of students (teacher trainee). Teaching skills were measured using two instruments with two different focus. The first is the student learning observation instrument (student-focused) and the second is an assessment instrument for teaching practices (focusing on the actions of the teacher trainee). From four teacher trainee of Biology Education FKIP UNEJ who had the opportunity to practice LS-based PPL in Junior High School 9 of Jember, all of them show improved teaching skills significantly. Keywords: teaching skills, PPL, lesson study